Recognition of spatial distribution of convergence fluctuation of VIMFC vertical cumulative moisture on Iran’s atmosphere during 1979-2013 - Farshad Pazhoh; mehry akbary; Mohammad Darand (تحقیقات کاربردی علوم جغرافیایی)
The aim of this study is to identify the spatial distribution of Vertically Integrated Moisture Flux Convergence (Vertically Integrated) Moisture Flux Convergence) on Iran’s atmosphere. To achieve this aim, the monthly ECMWF gridded data used during the period from 1/1979-12/2013. First, based on the specific humidity content in the atmosphere, troposphere divided into three layers (850-1000hPa), mid (700-775hPa) and upper (500-600hPa). In order to achieve VIMFC spatial variations on Iran, spatial self-correlation methods   of globular moron and hot spots used at 90, 95, 99 and 99/99 percent significance levels. The results of this study showed that the spatial distribution of VIMFC in Iran during the first layer of troposphere and especially during warm months of year has a high cluster pattern and in cold months of the year and in the third layer of troposphere cluster pattern decrease. Based on the hot spots index in the first layer of troposphere low height regions, in the second layer of troposphere the  high regions of the Alborz, zagros and central mountains and in the third layer of troposphere alpine regions of central and eastern Iran's mountains has positive spatial self-correlation (hot spots). The results show that in winter and autumn during the second period (1999-2013), the range of hot spots of the VIMFC show a significant reduction compared to the first period (1979-1998) on Iran.